Defeitos FeN4 em nanoestruturas de carbono: um estudo comparativo com as moléculas Fe-porfirina e Fe-ftalocianina - Ingrid Carolina Ibagon Pardo (2010)
In this dissertation we conducted a comparitive study between the Fe-porphyrin and Fe-phthalocyanine molecules and carbon nanostructures with FeN4 defects using first-principles calculations based on the Density Functional Theory. For all systems, we performed calculations varying the total charge. In the case of Fe-porphyrin and Fephthalocyanines we studied the neutral systems and those resulting from the addition or remotion of one electron and, in the case of the carbon nanostructures we added a quantity of charge per carbon atom equivalent to each case studied for the molecules. We observed a tendency of the iron atom to mantain its charge constant when the total charge of the system changes, while the spin magnetic moment of the system changes with the total charge. The systems have spin magnetic moment equal to 2uB when they are neutral, but it increases (decreases) when electrons are removed (added) from (to) the system. Due to the importance to the biochemistry of hemoproteins and to the fabrication of fuel cells, we also studied the binding of the O2 molecule to Fe-porphyrin and to C60 fullerene with the FeN4 defect. We observed that for both molecules the ground state of the complex bound to the O2 molecule is a singlet. It is characterized by the antiferromagnetic coupling between one electron localized in the iron atom and another localized in the O2 molecule, and a sigma bond resulting from the combination of the dz2 orbital from the iron and the antibonding orbital from the O2 molecule. After binding to the fullerene or to the Fe-porphyrin, the O2 molecule can be dissociated by a second interaction with another fullerene or a Fe-porphyrin molecule, respectively. The binding of the O2 molecule to N4H2 defect in the fullerene was also studied. We observed that, in this case, the binding energy of the O2 molecule is 0.9 eV less than that of the FeN4 defect, and that the O2 molecule dissociates after a second interaction with another fullerene, producing two water molecules with the hydrogen atoms from the N4H2 defects.